TINDAK TUTUR DIREKTIF GURU DALAM PEMBELAJARAN BAHASA ARAB - Qomariyah, Lailatul (Arabi : Journal of Arabic Studies, 2017)
This research investigates teachers’ directive speech act in Arabic Language Teaching. The research was applied through pragmatic approach using the theory of Bach and Harnish’s speech act and Yule’s speech act strategy. The research instrument is in the form of teachers’ speech containing directive meaning. Based on the analysis, it can be concluded that: (1) first, the category of teacher’s directive speech act in Arabic language teaching at MAN 1 Jombang involves requesting, advising, commanding, challenging, inviting, daring, and entreating directive speech acts, (2) the speech acts were delivered in directive or underactive with various motives. The results are expected to be useful to be referred in using directive speech acts whether its category or strategy in Arabic language learning. Thus, the communication between teachers and students can be more interactive and meaningful. Therefore, this research is needed to conduct.